1967
DOI: 10.1177/004051756703700704
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Various Combinations of Chemical and Physical Treatments on the Physical Properties of Cotton Yarns and Bundles

Abstract: The effects of tension during resin treatment on the physical properties of yarns and fibers that had received various combinations of pretreatments were investigated for Pima, Bobshaw, and Deltapine cottons. Pretreatments included scouring, mercerization, and acid degradation. Dimethylolethyleneurea (DMEU) resin was applied at 2 and 5% add-on. Relationships between bundle and yarn tensile properties were studied and found to have high correlation. Some evidence was found that degradation prior to tension duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1968
1968
1991
1991

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The influences of fiber length on toughness appear to diminish as strength is decreased or rigidity of fiber structure is increased by crosslinking treatment. The relationships of fiber-bundle toughness to yarn toughness for three cottons differing in chemical and mechanical treatments have been reported [5]. The pattern of relationship for Pima cotton with long fibers followed that established by the Bobshaw and Deltapine 15 cottons having fibers of comparable lengths.…”
Section: Cottons and Fabricsmentioning
confidence: 89%
“…The influences of fiber length on toughness appear to diminish as strength is decreased or rigidity of fiber structure is increased by crosslinking treatment. The relationships of fiber-bundle toughness to yarn toughness for three cottons differing in chemical and mechanical treatments have been reported [5]. The pattern of relationship for Pima cotton with long fibers followed that established by the Bobshaw and Deltapine 15 cottons having fibers of comparable lengths.…”
Section: Cottons and Fabricsmentioning
confidence: 89%
“…[8] and Rebenfeld [103, among others, found that tension during the resin treatment reduced the strength loss caused by the resin treatment. Others [1, 3,5,9,11,13] have . found that swelling and stretching before resin treatments can improve the strength of fibers and yarns and improve the strength retention after resination.…”
mentioning
confidence: 99%